(untitled) (Research, Society and Development, 2022)
Objective: The aim of this study was to determine the correlation between the distance from the file tip to the apical foramen and the readings on displays of two Electronic Apex Locators. Methodology: 46 human teeth were accessed, and electronic measurements were obtained at the display levels: 2.0; 1.5; 1.0; 0.5 and “apex”, these electronic measurements were repeated. Results: At the 0.0 and 0.5 display numbers, there was an accurate detection of the apical foramen: 93.5% for the Root ZX II and 93.5% for the RomiApex A-15 (± 0.5 mm). Analysis of variance (ANOVA) revealed that the accuracies of the two devices did not differ (p>0.05). At 2.0, 1.5 and 1.0, the accuracy was low and there was a significant difference in the accuracy of booth devices (p=0.000). When evaluating repetition of measurements, there was a high level of reproducibility (the ICCs ranged between 1.000 and 0.992 for the Root ZX II and between 1.000 and 0.989 for the RomiApex A-15) in all evaluated display’s levels. Conclusions: Both devices displayed high accuracy and reproducibility at the 0.0 and 0.5 display numbers.